EFEKTIFITAS PELAKSANAAN PROGRAM PENGUATAN KAPASITAS KESIAPSIAGAAN DAN TANGGAP DARURAT BENCANA (LEARN II) OLEH HEKS DAN YAYASAN HOLI ANA’A - Steady Novrianto ZALUKHU (Welfare StatE, 2013)
Pay close atention to condition of geographical, geologic, hydrologic and demography, in the fact Indonesia has highly prone to consist of disaster which caused of nature, unnature even human. On December, 26th 2004 a huge earthquake occured in north coastal area of Sumatera Island which took more than 220.000 victims. Non Government Organization is known have a big role after disaster occured because normally NGO is close to the people who got the impact. Therefore, by those LEARN II Project NGO who got the learning is expected can spreading out knowledge of disaster to the people so that they can also behave and more prepared when disaster comes. The goal of this reasearch study is to know about how far effectivness the implementation of LEARN II Project by HEKS and Holi ana’a Foundation. The result of this research study is expected to be refrence in order to develop concept and theory related to Disaster Risk Reduction and Emergency Response.. This research study was held in The Center of Disaster Risk Development Management HEKS coordinated with Holi ana’a Foundation which located in Medan that also named with Head Office of LEARN Project. Population in this research study consists on LEARN II member per a year starting from July 2012 until June 2013 who included in first cycle until sixth cycle learning and total member is 46 NGOs. The type of this Research is descriptive with qualitative approach. To obtain necessary data, this research study using data collection technique and field study which consists of questionnaire, interview and observation. Based on the result of data analysis, it was found that the implementation of LEARN II project is effective. There was an increase of capacity of preparedness and disaster emergency response to member of NGO after participate the LEARN II Project. LEARN II Project also results trained personal who include directly to the people when disaster occured. Key words : effectiveness, disaster risk reduction and emergency response, LEARN II